Navigating Do-Not-Attempt-Resuscitation decisions in emergency department in Malaysia: A retrospective study - Chew, Keng Sheng; Madeleine Kho, Huei Tze; Yang, Xiang Yun (Malaysian Medical Association, 2024)
Introduction: The practice of Do-Not-Attempt-Resuscitation (DNAR) aims to respect patient autonomy and acknowledge medical futility. Despite its global acceptance, there is limited research on DNAR in many Asian countries, including Malaysia. This study addressed this gap by exploring DNAR decision-making processes in a Malaysian tertiary hospital. Materials and Methods: A mixed-method retrospective study was conducted in the emergency and trauma department (ETD) of Sarawak General Hospital, Malaysia, from February to July 2023. Data were collected from 115 DNAR cases using a surveillance form to document the patient demographics, types of DNAR orders, initiating physicians, reasons for DNAR, surrogate decision-makers, specific types of procedures withheld or withdrawn and outcomes. Thematic analysis was used for qualitative data, while inferential statistical analysis was applied to quantitative data. Results: The mean age of patients was 71.32 years, with a male predominance (63.5%). The primary reasons for DNAR included “critical illness with poor prognosis” (33.9%), “advanced age with frailty and poor prognosis” (20.9%) and “massive haemorrhagic or ischemic stroke” (16.5%). Most DNAR decisions involved withholding resuscitation (90.4%) and were initiated mainly by internal medicine (52.2%) and emergency medicine teams (34.8%). Surrogate decisionmakers were predominantly adult children (63.5%). Only one case had an advance directive. Majority of patients (80.9%) were admitted to wards, while 16.5% died in the emergency department. The median age of patients was significantly older when adult children (78 years) and spouses (76 years) were the surrogates, compared to when they were not involved (64.5 years and 62.5 years, respectively; p < 0.001 and p = 0.003, respectively). Conversely, the median age was significantly younger when parents (41.5 years) and siblings (64 years) were the surrogates, compared to when they were not involved (75 years and 74 years, respectively; p < 0.001 for both). Conclusion: Advanced directives are rarely applied in Malaysia. DNAR decisions are typically made by surrogates when patients are critically ill, which is a common trend in many Asian cultures where discussing death is taboo. Cultural norms often lead families to withhold terminal diagnoses from patients, posing challenges for end-of-life care. The most frequent surrogates were adult children, who face dilemmas balancing aggressive treatment and their parents’ wishes. The study underscores the need for better communication and decision-making support in emergency departments.